2021
DOI: 10.1177/17479541211020418
|View full text |Cite
|
Sign up to set email alerts
|

Estimating somatic maturity in adolescent soccer players: Methodological comparisons

Abstract: Purpose Monitoring maturation facilitates effective talent development. Various methods of maturity estimation exist with limited knowledge of concordance between methods. This study aims to establish agreement between methods of varied constructs to predict maturity status and compare concordance of methods to categorise players using established thresholds. Methods This study compared four maturity equations using anthropometrical data from 113 male adolescent soccer players (mean ±SD; age, 14.3 ± 1 years) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 30 publications
(81 reference statements)
1
23
0
Order By: Relevance
“…Parr, Winwood [ 46 ] showed that 96% of a sample of professional academy soccer players experienced PHV during the specified window (85–96% PAH) in comparison to only 61% using the maturity offset approach (± 1-year generic age) [ 46 ]. With Salter, Cumming [ 47 ] having also showed some disparity in agreement between maturity offset and PAH methods (–1.5 to 1 year). That said, although the Khamis and Roche [ 19 ] method has been recognised by researchers and practitioners (including the present study) [ 6 , 46 , 47 ] as being the most suitable equation for estimating the maturity status of academy soccer players, practitioners should be aware that prediction error also manifests within the Khamis and Roche [ 19 ] method with median error being reported as 2.4–2.8 cm to 5.5–7.3 cm for those children who are situated on the 50th and 90th normative growth percentiles respectively (see Towlson, Salter [ 6 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Parr, Winwood [ 46 ] showed that 96% of a sample of professional academy soccer players experienced PHV during the specified window (85–96% PAH) in comparison to only 61% using the maturity offset approach (± 1-year generic age) [ 46 ]. With Salter, Cumming [ 47 ] having also showed some disparity in agreement between maturity offset and PAH methods (–1.5 to 1 year). That said, although the Khamis and Roche [ 19 ] method has been recognised by researchers and practitioners (including the present study) [ 6 , 46 , 47 ] as being the most suitable equation for estimating the maturity status of academy soccer players, practitioners should be aware that prediction error also manifests within the Khamis and Roche [ 19 ] method with median error being reported as 2.4–2.8 cm to 5.5–7.3 cm for those children who are situated on the 50th and 90th normative growth percentiles respectively (see Towlson, Salter [ 6 ]).…”
Section: Discussionmentioning
confidence: 99%
“…31 In instances where a biological parent was not in contact with a player and their parent/guardians, a national average for adult height was used for that biological mother or father. 32 The median error bounds between actual and predicted adult height using the Khamis–Roche method is 2.2 cm in males aged between 4 and 17.5 years. For the age groups examined in this study, 12–16 years, the lowest 50% error was 1.3 cm for 16 year olds, and the highest 50% error was 2.8 cm for 14 year olds.…”
Section: Methodsmentioning
confidence: 92%
“…Although previous research has recommended the use of plotted growth curves to estimate the status of an athlete relative to PHV (13,35,44), the accuracy of such assessments in classifying players as pre-, circa-, or post-PHV has not been evaluated. Results of the present study indicated substantial agreement and a high percentage of concordance with maturity status classification (pre-, circa-, post-PHV) based on complete growth curves using ±1and ±0.5-yr circa-PHV thresholds, recognizing the limitations of the narrow band.…”
Section: Discussionmentioning
confidence: 99%